Student - Initiated Curriculum Planning, Visualization And Assessment In A Ubiquitous Environment - Poursaeed, Bahar (2009)
This research studies the effectiveness, efficiency and acceptance of student initiated curriculum planning, visualization and assessment in a mobile and ubiquitous learning environment. The goal of the study is to identify necessary features to improve learning in mobile and ubiquitous learning environments, and understand how these methods and services should be distributed in the ubiquitous environment to achieve the best results.